EVALUATION OF THE NUTRITION CONTENT OF BROILER RATION STARTER PHASE FERMENTED USING LIGNOCELLULOLYTIC PROBIOTIC BACTERIA - M. A. R., Lisandy; Mudita, I M.; Suryani, N. N. (Jurnal Peternakan Tropika, 2022)
Efforts to improve broiler performance can be done by using fermentation technology on rations with lignocellulolytic probiotic bacteria. This research was carried out to know the nutritional content of the starter phase of broiler rations fermented using lignocellulolytic probiotic bacteria and know the best bacteria from the fermented rations. This study used a completely randomized design (CRD) with four treatments and four replications, namely fermented starter phase broiler ration without lignocellulolytic probiotic bacteria (RB0) inoculum, fermented starter phase broiler ration with Bacillus subtilis BR4LG (RB1) inoculum, broiler ration phase starter fermented with inoculum Bacillus sp. BT3CL (RB2), and fermented starter phase broiler ration with Bacillus sp. BT8XY (RB3). Each treatment added 5% inoculum. The variables observed were dry matter, organic matter, ash, crude protein, crude fiber, crude fat, and gross energy. The results showed that the use of lignocellulolytic probiotic bacteria in the diet was able to increase (P<0,05) the content of dry matter, ash, crude protein, crude fat, and gross energy (P>0,05), and decrease (P<0,05) content of organic matter and crude fiber in fermented rations without lignocellulolytic probiotic bacteria. Based on the results of the study, it can be concluded that the administration of lignocellulolytic probiotic bacteria has an effect on the nutritional content of the ration. The best bacteria in this study was Bacillus sp. BT3CL because it has highest nutritional content in crude protein content by 21,16% and gross energy of 3,92 kcal/gr, and the lowest nutrient content in crude fiber 2,48% and crude fat 10,37%. Keywords: lignocellulolytic probiotic bacteria, broiler ration starter phase, feed nutritional content.